I want you - Hanawalt, Lisa (Drawn & Quarterly, 2020)
"The stars here are She-Moose, who we join sex-toy shopping, and He-Horse, who we learn mid-flight suffers from ornithophobia. The true star of I Want You may just be Hanawalt's hilarious command of the graphic listicle. "Top Causes of Freeway Accidents" is a prescient pre-BoJack display of Hanawalt's love for all things equine. "Things We Are Sorry We Did Last Night" includes the murder of all Hanawalt's Google doppelgängers. Whether she's discussing the daily commute or masturbation, she packs each comic in I Want You with punchy cultural observations and sharp-witted reflections on typically taboo subjects. A master humorist, Hanawalt strikes the perfect balance between drawing the gorgeous and the repugnant, the fantastical and the lifelike, the bizarre and the hilarious--creating a deeply human experience that everyone can relate to"--Amazon.